Kondisi Struktur Tower Baja Terdampak Kebakaran Melalui Inspeksi Secara Visual - Zel Citra; Antonius Antonius; Biantoro, Agung Wahyudi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Building fires can significantly degrade the strength and integrity of steel structures, so post-incident evaluation is crucial to ensure building safety and feasibility. This study aims to evaluate the condition of the steel tower structure after the fire through a visual inspection method. A total of 35 structural elements were examined, including columns, beams, and bracing, to identify damage caused by heat exposure. The inspection results showed that 6 elements (17%) were in the category of Acceptable, 8 elements (23%) Needs Attention, 5 elements (14%) Not Acceptable, and 1 element (3%) Not Applicable because they had been removed. Steel columns generally remain upright without deformation, but suffer damage to the protective layer (coating). In contrast, most blocks lose their protective layers, are directly exposed to fire, show early signs of corrosion, and some suffer severe damage such as flange tears and cuts. These findings confirm the importance of systematic documentation and classification of element conditions as the basis for technical decision-making for structural improvement. Visual inspection proved effective as an initial step in the evaluation process, providing a relevant initial picture of the extent of damage and the need for intervention. This study recommends follow-up in the form of advanced structural analysis and material testing to ensure the feasibility of reusing the affected steel elements.